A Probable Way Vitamin D Affects Autism Spectrum Disorder: The Nitric Oxide Signaling Pathway - Wang, Bing; Dong, HanYu; Li, HongHua; Yue, XiaoJing; Xie, Lin (Frontiers in Psychiatry, 2022)
Vitamin D (VD) deficiency during pregnancy and early brain development is an important environmental risk factor for autism spectrum disorder (ASD). Its specific mechanism of action is still unclear. However, one study on the correlation between metabolomics and VD levels in children with ASD has found that the whole-blood arginine (Arg) levels of children with ASD are significantly negatively correlated with serum VD levels, suggesting that the effect of VD on ASD may be related to the signaling pathway involving Arg. Arg is a precursor of nitric oxide (NO), and changes in its levels most directly affect NO levels and signal transduction pathways. NO, a biologically active free radical, is both a neurotransmitter and a neuromodulator in the central nervous system and is related to the pathogeneses of various neurological diseases. The NO signaling pathway is not only affected by VD levels but also closely related to ASD through a series of mechanisms, such as neurotransmitter imbalance, immune disorders, and oxidative stress. Therefore, the effect of VD on ASD may be achieved via regulation of the NO signaling pathway. The current review discusses the relationship among VD, NO and ASD as suggested by a large body of evidence in the literature in an effort to provide clues for research on the pathogenesis of ASD and the mechanism of VD's impact on ASD.